Teachers' meetings an analysis of practices, content, purposes, and participant roles in selected public elementary schools of Quezon City - Gorospe, Cleofina R. 1922- ([Quezon City s.n.], 1964)
This study ascertains how teachers' meetings are planned and directed. This is concerned with the analysis of teachers' meetings in seven selected public elementary schools in Quezon City for the school year 1962-1963.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teachers' meetings; School management and organization